Fabrication and Application of Iron(III)-Oxide Nanoparticle/Polydimethylsiloxane Composite Cone in Microfluidic Channels. (30th December 2012) - Huang, Cheng-Chun; Wu, Ming-Dao; Liang, Dao; Yu, Jiashing; Shih, Po-Jen; Shih, Wen-Pin
Abstract : This paper presented the fabrication and applications of an iron(III)-oxide nanoparticle/polydimethylsiloxane (PDMS) cone as a component integrated in lab on a chip. The two main functions of this component were to capture magnetic microbeads in the microfluid and to mix two laminar fluids by generating disturbance. The iron(III)-oxide nanoparticle/PDMS cone was fabricated by automatic dispensing and magnetic shaping. Three consecutive cones of 300 μ m in height were asymmetrically placed along a microchannel of 2 mm in width and 1.1 mm in height. Flow passing the cones was effectively redistributed for Renolds number lower than 3.45 × 10 − 3 . Streptavidin-coated magnetic microbeads which were bound with biotin were successfully captured by the composite cones as inspected under fluorescence microscope. The process parameters for fabricating the composite cones were investigated. The fabricated cone in the microchannel could be applied in lab on a chip for bioassay in the future.